Stakeholders' priorities for management of a restored elk (Cervus canadensis) population in northeast Minnesota - Kyle A. Smith; Adam C. Landon; Eric M. Walberg; David C. Fulton; Michael W. Schrage; Nicholas P. McCann; James D. Forester (Conservation Science and Practice, 2025)
Abstract Wildlife reintroduction projects are an important tool for restoring traditional wildlife heritage, increasing species diversity, providing subsistence and sport hunting and other recreational opportunities, and assisting ecosystem adaption to future climate change. In Minnesota, the Fond du Lac Band of Lake Superior Chippewa and some conservationists advocate for the expansion of existing elk range to other parts of the state. For reintroduction projects to be successful, it is helpful if managers understand stakeholders' preferences for management objectives. We used best‐worst scaling (BWS) to assess residents' preferences for management objective alternatives. The University of Minnesota, in collaboration with the Fond du Lac Band of Lake Superior Chippewa and the Rocky Mountain Elk Foundation, conducted a mail‐back questionnaire of landowners (n = 4500) and the general public (n = 4000) in northeastern Minnesota to determine their attitudes toward elk reintroduction. Results suggest that the most preferred objectives were minimizing negative impacts on existing wildlife populations and reintroducing native species. In contrast, the least important objectives were related to providing elk viewing opportunities or maximizing economic opportunities through elk‐related tourism. These findings help inform management objectives related to the reintroduction proposal, provide insight to minimize potential conflict and help develop future communication material related to elk reintroduction.